Comparative study of tripartite identity-based authenticated key agreement protocols - Hölbl, Marko (Informatica (Ljubljana), 2009)
Podana je primerjava protokolov za izmenjavo ključev.
Keywords: informatika; information science; avtentičnost; identiteta; security; varnost